Patient satisfaction analysis: Identifying key drivers and enhancing service quality of dental care - Wen-Jen Chang; Yen-Hsiang Chang (Elsevier, 2013)
Background/purpose: Dental care service quality has received increasing attention in recent years. Patient satisfaction is extensively used to evaluate healthcare service quality. The aim of this study was to propose a conceptual framework for identifying the key drivers and provide guidance for enhancing dental care service quality. Materials and methods: The dentistry department of a typical Taiwanese hospital was investigated. In total, 400 adult patients, who subsequently visited the studied hospital for dental treatment, participated in this study. Donabedian's structure-process-outcome model was used to explore the dental care service elements. A Kano-type questionnaire was developed as the survey instrument. Results: The response rate was 76% (303/400). Cronbach's α value to each question was >0.7, implying that the questionnaire was highly reliable. When investigating 30 quality elements, based on Kano's perspective, 12 elements were classified into must-be attributes, which are regarded as key drivers of patient satisfaction; 10 elements were in the attractive attributes category; and the remaining were one-dimensional attributes. Patient responses to most dental service elements ranged from satisfied to very satisfied. Conclusion: Physical characteristics of structural aspects and administration of process aspects are regarded as essential dimensions. Patient satisfaction with the surveyed service elements was positive. Satisfaction with administration-related factors, other than accurate patient records, in the process aspect was at the lowest level, thus there should be opportunities for improvement.